Counteracting Climate Science Politicization With Effective Frames and Imagery. Issue 2 (April 2019) - Bolsen, Toby; Palm, Risa; Kingsland, Justin T.
Politicization of science occurs when the inherent uncertainty of science is emphasized to cast doubt on scientific consensus. Climate change has become particularly susceptible to this kind of politicization. In this article, we report the results of a survey experiment in which we manipulated text frames and visual imagery associated with two types of environmental hazards linked to climate change—sea level rise with associated flooding and increased heat levels with associated drought and wildfires. We present evidence that the use of visual imagery can counter the effects that science politicization has on climate change beliefs and behaviors.